BYOD Systematic Literature review: A layered approach - Ntwari , Richard; Habinka, Annabella E; Kaggwa, Fred (European Journal of Technology, 2022)
Introduction: Bring your own device (BYOD) is a paradigm where employees use personal devices for organizational related activities. Various benefits accrued by both employees and organization. However, BYOD leads to risks and threats during their usage. Purpose: The paper aimed at exploring benefits, risks, and suggested controls based on a systematic review of literature. Methodology: A systematic review methodology was adopted for the study. A search using keywords was conducted to select peer-reviewed journal papers from 2010 to 2020 in ACM Digital Library, Emerald Insight, IEEE Explorer, Science Direct, and Taylor and Francis. Inclusion and exclusion criteria was applied, followed by quality appraisal on the selected articles, and then the data was extracted. Results: According to the search results, BYOD research is on the rise. Benefits, risks, and controls associated with BYOD were also identified based on a layered approach. Findings indicate that user management is the weakest layer. Originality/value: This paper adds to previous research on BYOD practices by highlighting key risks and suggesting practices that organizations can use to manage security and privacy risks in BYOD environments using a layered approach.